Effect of aspect ratios of rutile TiO2 nanorods on overall photocatalytic water splitting performance. Issue 8 (13th February 2020) - Fu, Bing; Wu, Zhijiao; Cao, Shuang; Guo, Kai; Piao, Lingyu
Abstract : The spatial separation of reduction and oxidation reaction sites on the different facets of a semiconductor is an ideal and promising route for the overall photocatalytic water splitting due to efficient charge carrier separation. Abstract : The spatial separation of reduction and oxidation reaction sites on the different facets of a semiconductor is an ideal and promising route for overall photocatalytic water splitting due to efficient charge carrier separation. Rutile TiO2 has separate oxidation and reduction crystal facets and can be used to achieve direct splitting of pure water under ultraviolet (UV) light irradiation. In order to improve the rate of water oxidation reaction, the ratio of different crystal facets of rutile should be regulated controllably. However, the preparation of rutile TiO2 architecture has been limited by the availability of synthetic techniques. In this study, rutile TiO2 nanorods with various aspect ratios were accurately prepared in the presence of Cl − anions and H + cations, which were found to play a crucial role in forming the morphology of rutile TiO2 nanorods. In addition, the mechanism involving the growth of rutile TiO2 nanorods with different aspect ratios is proposed. Rutile TiO2 nanorods with a high proportion of oxidative (111) facets provided higher overall water splitting reactivity.